Prospekty, drobne katalogi, cenniki i ogłoszenia księgarskie" - H., Altenberg; K., Bartoszewicz; Sigmund, Bensiger; Franz, Bondy; Zygmunt, Celichowski; Fr., Chocieszyński; Józef, Chociszewski; Adolf, Gebethner Gustaw; Zygmunt, Gerstmann; Michał, Glücksberg; Gubrynowicz, Władysław Ludwik (1836-1914); J., Heumann K.; et al. (1882)
Altenberg H. (F. H. Richter), Lwów 1882-1889, (4), nr 5, 19, 118, 158. - Bartoszewicz K., Księgarnia, Kraków 1882-1883, (2), nr 15, 39. - Bensiger Zygmunt, Wiedeń ok. 1882, nr 17. - "Biblioteka Domowa", Gródek pod Lwowem, 1885-1886, (2), nr 81, 100. - "Bogarodzica", Gniezno 1885, nr. 79. - Bondy Franz, Wiedeń 1883, nr 40. - Chocieszyński Fr., Drukarnia, Poznań 1883, nr 36. - Chociszewski J., Gniezno, Poznań, ok. 1882-1888, (5), nr 20a, 44-45, 135, 144. - "Dom Polski", Poznań 1887-1888, (2), nr 124, 134. - Drukarnia "Kuriera Poznańskiego", Poznań 1887, nr 116. - "Dziennik dla Wszystkich", Warszawa 1886-1887, (3), nr 103, 122, 130. - "Dziennik Powieści", Kraków 1884, (2), nr 47, 50. - "Dzwonek Wielkopolski", Poznań 1886, nr 138. - "Echo Muzyczne, Teatralne i Artystyczne", Warszawa 1883-1884, (2), nr 24, 58. - "Ekonomista", Warszawa 1882, nr 9. - "Encyklopedia humoru", Warszawa 1889, nr 157. - "Gazeta Poznańska", Poznań 1888, nr 142. - Gebethner i Wolff, Warszawa 1882-1889, (9), nr 3, 31, 38, 54, 80, 102, 119, 140, 159. - Gerstmann Zygmunt, Berlin 1885, nr 64. - Glücksberg Michał, Warszawa 1882-1888, (7), nr 11, 32, 62, 85, 127, 148, 152. - "Głos Polski", Poznań 1886, nr 89. - Gubrynowicz i Schmidt, Lwów ok. 1885-1888, (2), nr 71, 149. - "Gwiazda Katolicka", Lwów 1889, nr 162. - Himmelblau J. M., Księgarnia wydawnicza, Kraków 1882, nr 10. - "Hodowca", Warszawa 1886, nr 101. - "Inżynieria i Budownictwo. Przemysłowiec wiejski", Warszawa 1885, nr 65. - "Jedność", Poznań 1888, nr 145. - Kamieński N. i Sp., Poznań 1883-1888, (5), nr 23, 49, 72, 97, 136. - "Katolik", Wydawnictwo, Bytom 1888-1890, (4), nr 133, 160, 167-168. - "Katolik Śląski", Bytom 1886, nr 94. - "Kłosy", Warszawa 1887, nr 128.
1000,00
Keywords: Bytom; wydawnictwo - "Katolik"; czasopismo - "Katolik Śląski"; Gniezno; Czasopismo - "Bogarodzica"; księgarnia - Lange J. B; Gródek; czasopismo - "Ognisko Domowe"; czasopismo - "Biblioteka Domowa"; Inowrocław; czasopismo - "Kujawiak"; Kraków; czasopismo - "Dziennik Powieści"; księgarnia - Himmelblau J. M; Księgarnia Katolicka Władysława Miłkowskiego; czasopismo - "Przegląd Powszechny"; czasopismo - "Missye Katolickie"; Towarzystwo Numizmatyczne; czasopismo - "Przegląd Polski"; księgarnia - Żupański J. K. i Heumann K. J; Towarzystwo Jezusowe; księgarnia - Bartoszewicz K; Lwów; czasopismo - "Przegląd Społeczny"; Zakład Artystyczno-Fotograficzny - Trzemeski Edward; czasopismo - "Różowe Domino"; czasopismo - "Gwiazda Katolicka"; księgarnia - Gubrynowicz i Schmidt; księgarnia - Altenberg H; Księgarnia Polska; czasopismo - "Przewodnik Gimnastyczny Sokół"; Mikołów; Księgarnia, Wydawnictwo Dzieł Ludowych - Miarka Karol; Ostrów; księgarnia - Leitgeber Mieczysław; Paryż; Zakład litograficzny - Piliński A. et Fils; Towarzystwo Historyczno-Literackie; Poznań; czasopismo - "Ziemianin"; Księgarnia Katolicka; księgarnia - Kozłowski Karol; Komitet redakcyjny jednodniówka "Okrężne"; Drukarnia Narodowa; czasopismo - "Kurier Poznański"; księgarnia - Kamieński N. i Sp; czasopismo - "Jedność"; czasopismo - "Kurier Rolniczy"; czasopismo - "Głos Polski"; czasopismo - "Gazeta Poznańska"; czasopismo - "Trud"; czasopismo - "Dzwonek Wielkopolski"; Drukarnia "Kuriera Poznańskiego"; czasopismo - "Dom Polski"; drukarnia - Chocieszyński Fr; czasopismo - "Nowa Gazeta Poznańska"; czasopismo - "Tygodnik Beletrystyczny i Naukowy"; drukarnia - Leitgeber Jarosław; księgarnia - Leitgeber Mieczysław i Sp; czasopismo - "Tygodnik Przemysłowy"; czasopismo - "Wielkopolanin"; księgarnia - Żupański Jan Konstanty; Strzelno; czasopismo - "Nadgoplanin"; Warszawa; czasopismo - "Echo Muzyczne, Teatralne i Artystyczne"; czasopismo - "Kurier Warszawski"; Komitet wydania dzieł Jan Kochanowskiego; czasopismo - "Kłosy"; czasopismo - "Inżynieria i Budownictwo"; czasopismo - "Hodowca"; księgarnia - Glücksberg Michał; księgarnia - Gebethner i Wolff; czasopismo - "Ekonomista"; czasopismo - "Dziennik dla Wszystkich"; czasopismo - "Niwa"; księgarnia - Lewental S; czasopismo - "Życie"; czasopismo - "Zdrowie"; czasopismo - "Wisła"; czasopismo - "Wiek"; czasopismo - "Wieczory Rodzinne"; czasopismo - "Tygodnik Mód i Powieści"; czasopismo - "Słowo"; czasopismo - "Romans i Powieść"; czasopismo - "Rola"; czasopismo - "Przemysłowiec"; czasopismo - "Przegląd Tygodniowy"; czasopismo - "Przegląd Pedagogiczny"; księgarnia - Paprocki Teodor i Ska; księgarnia - Orgelbrand Maurycy; Wiedeń; księgarnia - Bensiger Sigmund; księgarnia - Bondy Franz; Katalogi księgarskie; Księgarnie; Ogłoszenia; Prospekty